Digital psychosocial assessment: An efficient and effective screening tool. (28th December 2019) - Ho, Jane; Fong, Cameron K; Iskander, Andrew; Towns, Susan; Steinbeck, Katharine
Abstract : Aim: A large proportion of young people with chronic health conditions are surviving into adulthood. They face the same challenges as their healthy peers and are at increased risk of mental health problems. Psychosocial assessment is a crucial aspect of clinical care. Interviews using the internationally used and accepted HEEADSSS (home environment, education/employment, eating, peer‐related activities, drugs, sexuality, suicide/depression, and safety) framework require trained clinicians, rapid interpersonal engagement, time and manual documentation. HEEADSSS‐derived digital self‐report surveys can be initiated by non‐trained staff. This study compares the utility and information recorded using both methods. Methods: A retrospective analysis comparing documentation from HEEADSSS guided face‐to‐face interview and a digital survey tool was conducted using 146 records collected by the Trapeze transition service across the two locations of the Sydney Children's Hospital Network (NSW, Australia) between 2013 and 2016. A panel of four experts used an iterative process to identify 29 data verification points, falling into seven categories. Wilcoxon signed‐rank tests were used to compare category scores. Results: The digital survey took an average of 15 min and showed a significantly higher rate of disclosure across all psychosocial categories, particularly in the sensitive areas of emotions, drug use, sex and safety, compared to electronic medical record documentation of interview. Conclusions: Digital survey provided a time‐efficient psychosocial screening tool that was self‐administered, able to be introduced by non‐trained staff, had a consistent record of responses, and elicited a substantially higher disclosure rate for important areas of strength and risk that may otherwise be avoided or not recorded.